The art of debugging with GDB, DDD, and Eclipse - Matloff, Norman S. (No Starch Press, 2008)
The Art of Debugging illustrates the use of three of the most popular debugging tools on Linux/Unix platforms: GDB, DDD, and Eclipse. In addition to offering specific advice for debugging with each tool, authors Norm Matloff and Pete Salzman cover general strategies for improving the process of finding and fixing coding errors, including how to inspect variables and data structures, understand segmentation faults and core dumps, and figure out why your program crashes or throws exceptions. You'll also learn how to use features like catchpoints, convenience variables, and artificial arrays and.